The Relationship Between Knowledge Level and Anxiety Level During CT Scan Examinations at the Radiology Department of Level II Prof. Dr. J. A. Latumetten Hospital - Niwele Amelia; Malisngorar Maritje; Niwele Dea (International Journal of Health Engineering and Technology, 2026)
Computed Tomography (CT) Scan is a diagnostic imaging procedure that combines X-ray technology and computer processing to produce detailed cross-sectional images of the human body. Despite its diagnostic benefits, undergoing a CT Scan can provoke anxiety in patients, often due to limited understanding of the procedure, concerns about radiation exposure, and uncertainty regarding the examination results. Elevated anxiety levels may compromise patient comfort and interfere with the examination process. This study aimed to examine the relationship between patients’ knowledge about the CT Scan procedure and their anxiety levels during examinations at the Radiology Department of RUMKIT TK II Prof. Dr. J.A. Latumeten. A quantitative research design with a cross-sectional approach was employed. Total sampling was used, involving 30 patients who underwent CT Scan examinations. Data were collected using structured questionnaires and analyzed using the Chi-Square statistical test to determine the association between knowledge and anxiety levels. The results indicated that there was no significant relationship between patients’ level of knowledge and their anxiety during CT Scan examinations, as evidenced by a significance value of 0.674, which is greater than the 0.05 threshold. This finding suggests that patients’ knowledge alone does not significantly influence anxiety levels during the procedure. Other factors, such as prior experiences with medical imaging, current health conditions, and environmental or staff support, may also play a role in shaping patients’ anxiety. In conclusion, while knowledge about the CT Scan procedure is important, it does not appear to directly reduce patient anxiety. Health practitioners should consider a holistic approach, addressing psychological, environmental, and experiential factors to minimize anxiety and improve patient comfort and cooperation during CT Scan examinations.